Identifikasi Kontaminasi Bakteri Staphylococcus aureus pada Daging Sapi di Pasar Kota Binjai - Asmaq , Nur; Nasution , Rahmad Hidayat (Journal of Pharmaceutical and Sciences, 2025)
Livestock products are generally very easily contaminated by bacteria because they contain high nutritional value, especially protein. This study aimed to identify Staphylococcus aureus contamination in beef samples taken from traders at Tavip Market and Kebun Lada Market in Binjai City. The study used 13 beef samples collected through a random sampling method. Each sample weighed 100 grams and was taken with sterile equipment, then transported in a cool box at a low temperature of approximately ±4°C. Other materials used included Buffer Peptone Water (BPW), Baird Parker Agar (BPA), and Coagulase Rabbit Plasma (CRP), which are specific media for S. aureus. Total Counting of S. aureus Bacterial Colonies Using the Total Plate Count (TPC) Method. The results showed that all 13 samples tested positive for S. aureus contamination, exceeding the Indonesian National Standard limit of 10² CFU/g, with the highest colony count reaching 2.9 × 10⁴ CFU/g. This indicates that the level of S. aureus bacterial contamination exceeds the Indonesian National Standard (SNI) limit, necessitating improved sanitation and hygiene in the market. Consumers are advised to thoroughly cook meat before consumption.